Anemia‐induced liver injury: A rare case revealing glucose‐6‐phosphate dehydrogenase deficiency. Issue 4 (15th March 2021) - Zaimi, Yosra; Ayari, Myriam; Mensi, Asma; Chelbi, Emna; Ayadi, Shema; Said, Yosra; Mouelhi, Leila; Debbeche, Radhouane
Abstract: Hypoxic hepatitis may occur due to hemodynamic mechanisms of hypoxia secondary to anemia without any context of reduced blood flow, respiratory failure, or shock state. Etiology of anemia should be investigated in order to avoid recurrence. Abstract : Hypoxic hepatitis may occur due to hemodynamic mechanisms of hypoxia secondary to anemia without any context of reduced blood flow, respiratory failure, or shock state. Etiology of anemia should be investigated in order to avoid recurrence.